The Effectiveness of English Language Podcast in enhancing Listening Skill - Astri, Astri; Kamaruddin, Abd; Arid, Muhammad; Dewi, Anjar Kusuma (Institut Agama Islam Negeri (IAIN) Curup, 2025)
This study aims to evaluate the effectiveness of English language podcasts in enhancing the listening skills of grade XI students at SMA Negeri 2 Palu. The research employed a pre-experimental design using a one-group pre-test and post-test approach. A total of 34 students from class XI E participated as the sample. To assess students’ initial listening proficiency, a pre-test was administered prior to the treatment. The treatment consisted of listening sessions using selected English podcasts from the YouTube channel “Easy English.” Following the treatment, a post-test was conducted to measure any improvements in students’ listening comprehension. The results indicated a significant increase in the average scores, rising from 64.41 in the pre-test to 81.91 in the post-test. Statistical analysis using the Wilcoxon Signed-Rank Test confirmed a significant difference (p < 0.05) between the two sets of scores. These findings suggest that English podcasts are effective learning tools for developing students’ listening skills. Their authentic and engaging nature, along with their flexible accessibility, makes podcasts a valuable supplement in English language instruction, particularly in fostering listening comprehension.